The effect of flooding and sodium chloride on the development of Amblyomma Variegatum (Fabricius, 1794) (Acarina: Ixodidae) (1993)
The effect of flooding in water and sodium chloride were investigated to establish ecological factors that limit the widespread distribution of Amblyomma variegatum in some localities. Sample of replete adults, eggs, and larvae of A. variegatum were immersed in 500ml of water for different durations (3, 6, 12, 24, 48, 72 and 96h), then dried and incubated at 25 °C, 85% RH. A second batch was immersed in 500ml of different sodium chloride concentrations (0, 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100%) for periods as stated earlier and thereafter incubated. They were observed for preoviposition time, ovipositional pattern and time of egg eclosion. Result showed that replete females died only after 24 h flooding in water. Eggs were most resistant to flooding. Replete females and larvae were more tolerant to NaCl solution than the eggs.